The Influence of Organizational Commitment and Job Satisfaction on Employee Performance Through Work Motivation as a Mediating Variable - Putra, Ilhami (UPI YPTK Journal of Business and Economics, 2022)
This study aims to prove and analyze the effect of organizational commitment and job satisfaction on employee performance through motivation as an intervening variable. In this study, several employees of the Jambi Provincial Education Office were selected as samples using a purposive sampling method. The data analysis technique used in this research is path analysis or Structural Equation Model (SEM) which is processed using Smart PLS. Based on the results of hypothesis testing, it was found that organizational commitment and job satisfaction had a positive and significant effect on the work motivation of Jambi Province Education Office employees. At the hypothesis testing stage it was also found that organizational commitment, job satisfaction and motivation had a positive and significant effect on the performance of Jambi Province Education Office employees. Besides that, in testing the indirect effect, it can be proven that motivation is able to mediate the relationship between organizational commitment and job satisfaction with the performance of Jambi Provincial Education Office employees.